The IL-33/sST2 Axis in Thromboangiitis Obliterans - Sharebiani H; Mohareri M; Mirhosseini A; Fazeli B (Dove Medical Press, 2020)
Hiva Sharebiani,1 Mehran Mohareri,1 Ali Mirhosseini,1 Bahare Fazeli1,2 1Immunology Research Center, Inflammation and Inflammatory Diseases Division, School of Medicine, Mashhad University of Medical Sciences, Mashhad, Iran; 2Vascular Independent Research and Education, European Foundation, Milan, ItalyCorrespondence: Bahare FazeliImmunology Research Center, Inflammation and Inflammatory Diseases Division, School of Medicine, Mashhad University of Medical Sciences, Mashhad, IranTel +985138002379Fax +985138414499WhatsApp ID +98 9151108249 Email bahar.fazeli@gmail.comBackground: Until recently, it remains unknown whether thromboangiitis obliterans (TAO) is a type of systemic vasculitis. A high level of IL-33 and its soluble decoy receptor sST2 in the acute phase of systemic vasculitis has been demonstrated.Methods: The serum level of IL-33 and sST2 in 50 TAO patients, 20 age- and smoking habit-matched controls and 19 age-matched non-smoker controls was evaluated.Results: The mean level of IL-33 in TAO, smokers and non-smokers was 370.2± 61.7ng/mL,132.14± 2.6ng/mL and 11.3± 0.38ng/mL, respectively. The IL-33 was significantly higher in the TAO than in either control groups (p < 0.001). The IL-33 in the acute phase of TAO was significantly higher than in the patients in the quiescent phase of the disease (p = 0.019). Also, IL-33 in the patients with gangrene was significantly higher than in the patients with non-healing ulcers (p = 0.021). The sST2 in the TAO patients was 49.3± 5.58ng/mL, and in smoker and non-smoker controls, it was 45.3± 6.3ng/mL and 4.11± 0.17ng/mL, respectively. No significant difference was found between the patients and smoker control groups (p = 0.87). The mean ratio of IL-33/sST2 was 27.89± 10.44 in the TAO group and, in smokers and non-smokers, it was 2.85± 0.48 and 2.84± 0.14, respectively. A significantly high level of IL-33/sST2 ratio was observed in TAO patients in both the active and quiescent phases of the disease in comparison to both control groups (p< 0.001).Conclusion: The regulation pattern of IL-33/sST2 was different in TAO in comparison to autoimmune vasculitis.Keywords: interleukin 33, soluble ST2, Buerger’s disease, thromboangiitis obliterans, vasculitis